The application of Al-Uqubat in the contemporary society: a re-examination using the maqasid Al-Shari'ah based schemes (2011)
This paper focuses on the complexity of the implementation of the Islamic criminal law with particular reference to the feminist view that the Islamic law is “the cornerstone of the system of male privilege set up in Islam” and that the preservation of this system of Islamic law in most Muslim countries signals the existence of anti-human rights practices that uphold not only oppression and domination of women but also of non-Muslims and even ordinary Muslims. Nevertheless, there still appears to be a serious misinterpretation of the Islamic penal code. This misinterpretation is due to the failure of Muslim scholars over the years to question the application of the Islamic penal law system in many Muslim countries, including Nigeria in line with the maqasid al-shari‘ah (the ultimate objectives of the Islamic law). This paper will ground itself upon maqasid al-shari‘ah in order to differentiate between the authentic scope and application of the Islamic criminal law and what is currently operational in the Muslim world.